Female entrepreneurship in Poland - GAWEŁ, Aleksandra (Economics and Business Review, 2025)
The aim of this paper is to present the issues connected with female entrepreneurship and in particular to analyse the changes in the rates of female entrepreneurship in Poland between the years 1993 and 2010 against the background of the job market situation, as well as identifying the factors which determine the entrepreneurship of women. The dynamics of female entrepreneurship will be contrasted with entrepreneurship among men. The entrepreneurship gender gap in Poland only slightly decreased during the studied period even though the situation of women in the job market is more difficult than that of men, which could engender a negative entrepreneurial motivation. The results of the research show that female entrepreneurship is signifi cantly more susceptible to the influences of the general market situation, measured by GDP, than the entrepreneurship of men. This means that the entrepreneurship gender gap can decrease only when there is long-term economic growth.